A Framework-based Approach for the Integration of Web-based Information Systems on the Semantic Web - Celino, Danillo R.; Reis, Luana Vetter; Martins, Beatriz Franco; Souza, Vítor E. Silva (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
For the vision of the Semantic Web to become a reality and its benefits harnessed, data available on the Web must also be published in the form of linked data. Moreover, the quality of the abstract conceptual models behind this data, i.e., their ontology, can also have a big influence in the adoption of linked data sets and their vocabularies. In this paper, we propose FrameWeb-LD, an approach for the integration of Web-based Information Systems on the Semantic Web, which uses well-founded languages and methods for the modeling of ontologies and aids developers in publishing their application’s data and services on the Web of Data.